Absorption-Dominant mmWave EMI Shielding Films with Ultralow Reflection using Ferromagnetic Resonance Frequency Tunable M-Type Ferrites - Horim Lee; Seung Han Ryu; Suk Jin Kwon; Jae Ryung Choi; Sang-bok Lee; Byeongjin Park (Nano-Micro Letters, 2023)
Highlights A novel multi-band absorption-dominant electromagnetic interference (EMI) shielding film with transition metal-doped M-type strontium ferrites composite layer and a conductive grid is developed. This film shows (1) ultralow EMI reflection less than 5%, (2) in multiple mmWave frequency bands corresponding to ferrites and grid characteristics, (3) with a broadband EMI shielding performance over 99.9% from 40 to 90 GHz.